A Female with Unilateral Facial Discoid Lupus Erythematosus-An Unusual Presentation: A Case Report in Bangladesh: Unilateral Facial Discoid Lupus Erythematosus-An Unusual Presentation - Afroz, Farzana; Naznin, Tamanna; Islam, Tawfique Raffat; Razzaque, Sabrina; Choudhury, Tamanna (Journal of the Medical College for Women & Hospital, 2025)
Lupus erythematosus (LE) is a chronic autoimmune disease with a diverse array of clinical illness among which Discoid Lupus Erythematosus (DLE) is one of the commonest forms involving the integumentary system mostly. Usually, classic DLE lesions exhibit some common features like discoid shape, dyspigmentation, adherent scale and atrophy, but sometimes these classic scenario may be absent. In case of atypical presentation, clinical assessment of the disease may aid in early diagnosis and prompt treatment of the condition. This would help prevent disfigurements, progression to systemic disease and poor quality of life. In our case, the patient presented with unilateral, asymptomatic plaque on her left malar region for last 15 years. The diagnosis was delayed due to unusual presentation and final conclusion was drawn by means of histopathological examination. J Med Coll Women Hosp.2025; 21 (1):95-99